2012
DOI: 10.1111/epp.2581
|View full text |Cite
|
Sign up to set email alerts
|

Tuta absoluta (Meyrick) (Lepidoptera, Gelechiidae) in the Republic of Srpska (Bosnia and Herzegovina)

Abstract: Pheromone traps were placed in the market place in Banja Luka, and in greenhouses and open field tomato crops, on 13 September 2010 to determine the presence of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) in Banja Luka region. Based on examination of traps, the presence of T. absoluta was confirmed for the first time in the Republic of Srpska. Only mines of Liriomyza species were found by examining leaves under a stereomicroscope. In 2011, pheromone traps were placed in greenhouses at several locations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…On the other hand, this survey confirmed that the pest is also present in greenhouses and open fields in the continental climate of B&H, such as in Bijeljina, Novi Grad, Banja Luka, Prijedor and Gradiška. In accordance with many authors ( VAN DEVENTER 2009, cited in BETTAIBI et al 2012, TOŠEVSKI et al 2011, ĐURIĆ et al 2012, this is partly caused by the intensive tomato production in some areas, as well as the cross-border tomato trade in the country.…”
Section: Distribution and Pheromone Trappingsupporting
confidence: 76%
“…On the other hand, this survey confirmed that the pest is also present in greenhouses and open fields in the continental climate of B&H, such as in Bijeljina, Novi Grad, Banja Luka, Prijedor and Gradiška. In accordance with many authors ( VAN DEVENTER 2009, cited in BETTAIBI et al 2012, TOŠEVSKI et al 2011, ĐURIĆ et al 2012, this is partly caused by the intensive tomato production in some areas, as well as the cross-border tomato trade in the country.…”
Section: Distribution and Pheromone Trappingsupporting
confidence: 76%